THE XIONGCUN COPPER-GOLD DEPOSIT IN TIBET: CHARACTERISTICS, GENESIS AND GEODYNAMIC APPLICATION - Xu W.; Cui Y.; Chen W.; Yang D.; Lian Y.; Qu X.; Yang Z.; Hou Z.; Pan F. (My University, 2006)
According to the alteration and mineraliazation assemblage, mineralizations in Xiongcun deposit can be obviously distinguished into two styles, i. e. early veinlet-disseminated Cu(Au) mineralization with associated albitization, local K-silicate alteration, andalusite alteration, extensive phyllic alteration and peripheral widespread propylitization, and late vein-style Au (Ag) -polymetallic mineralization with associated strong silicification, chloritization and kaolinization. The latter overprints the former. The H, O and S isotopic compositions and the high salinities of fluid inclusions indicate the magmatic contributions and the increasing contents of meteoric water in the mineralizing system from early to late. The early veinlet-disseminated Cu (Au) mineralization is similar to porphyry-type mineralizaiton and maybe belongs to an immature porphyry system. The late vein-style Au (Ag)-polymetallic mineralization, characterized by high salinity and high base metal contents, belongs to the transitional system between end-member high- and low-sulfidation-type epithermal systems. Xiongcun deposit is a telescoping system of above two. Sericite 40Ar/39Ar dating reveals the ore-forming age of Xiongcun deposit is 38.11±0.9Ma. K-feldspar K-Ar age of the K-feldspar-muscovite-tourmaline-pyrite pegmatoid dyke in Xiongcun is 47.62±0.7 Ma. These ages indicate that the mineralizing system in Xiongcun results from the intervallic relaxation (ca. 52~40 Ma) of the Himalayan-Tibetan orogen and the final telescoping from the proceeding rapid uplifting (40~38 Ma) of the orogen.
Keywords: 40AR/39AR DATING; HIMALAYAN-TIBETAN OROGEN; TELESCOPING DEPOSIT; XIONGCUN